Aktivitas Dakwah K.H. Muhammad Yahya di Cimahi Tahun 1947-2009 - Hendro Kartika; Ajid Thohir (UIN Sunan Gunung Djati Bandung, 2019)
K.H. Muhammad Yahya (commonly known as Abuya Sepuh or Abuya Mamad) is an Islamic scholar from Cimahi. He is a Da'i, Murshid Tariqah, and also a Judge in the Religious Courts. He was the founder of Pesantren Darussurur Cimahi, and extensively wrote Sundanese nadhom, and participated in spreading the Islamic da'wah in the City of Cimahi. He contributed to education, social, religion, and Islamic da’wah. This study aims at finding out the biography of K.H. Muhammad Yahya and his Da'wah Activities in Cimahi. The method used is a historical research method which consists of four stages, namely heuristics, criticism, interpretation, and historiography. Based on the results of the study, it can be concluded that, first, K.H. Muhammad Yahya was born in 1917 and died in 2009 in the Main Village, Cimahi. He is the son of K.H. Muhammad Azhari and Hj. Khadijah, his nasab through his father reached Maulana Syarif Hidayatullah. His educational genelogy was formed from the environment and education he got from various teachers, such as Habib Ali al-Attas (Jakarta), Habib Abdullah Bilfaqih (Malang), Muhaddist Assayid Alwi bin Abbas al-Malik (Mecca), K.H. M. Kurdi (Cibabat), K.H. M. Zarkasyi (Cibaduyut). Second, the da'wah activities K.H. Muhammad Yahya in Cimahi covers several aspects and media, namely da’wah through educational institutions with the establishment of pesantren Darussurur (1947-2009), da’wah through religious teachings (1947-2009), da’wah through Tariqah (TQN) (1960s), and da’wah through writing (1979-2009), in which he wrote and translated Arabic books composed in the form of Sundanese nadhom, such as Nadhom Shoibul Iman, Aqidatul awam, Lawang Setan, and many others.